Epitaxial GeSn: impact of process conditions on material quality. (16th October 2018) - Loo, Roger; Shimura, Yosuke; Ike, Shinichi; Vohra, Anurag; Stoica, Toma; Stange, Daniela; Buca, Dan; Kohen, David; Margetis, Joe; Tolle, John
Abstract: The electrical and optical material properties of epitaxial Ge1−x Snx and Siy Ge1−x−y Snx are of high interest for novel device applications. However, the limited Sn solubility in Ge makes the epitaxial growth of Ge1−x Snx and Siy Ge1−x−y Snx challenging. Most of the literature describing the epitaxial growth is for Ge2 H6 and SnCl4 as Ge and Sn precursors, respectively. A more recent publication deals with the epitaxial growth of high-quality Ge1−x Snx with the more conventional GeH4 . In this manuscript, we compare the structural and optical material quality of Ge1−x Snx, epitaxially grown on Ge virtual substrates as a function of growth pressure, growth temperature, the choice of the carrier gas (H2 or N2 ) and the choice of the Ge precursor (GeH4 versus Ge2 H6 ). The best material quality in terms of surface morphology and photoluminescence characteristics is obtained if GeH4 is used as a Ge precursor. For Ge1−x Snx grown with Ge2 H6 and at atmospheric pressure, pyramidical defects can be seen and there is a risk for uncontrolled local Sn agglomeration. The pyramidical defects are not observed on Ge1−x Snx layers grown at reduced pressure, but the highest achievable substitutional Sn concentration is lower. No pyramidical defects are found for Ge1−x Snx layers grown with GeH4 and the issue of uncontrolled local Sn agglomeration does not appear.